Feasibility of Discovery Learning Based Student Worksheets on Acid-Base Materials to Practice Critical Thinking Skills - Putri, Reyna Miftahud Daroeni; Yonata, Bertha (Hydrogen: Jurnal Kependidikan Kimia, 2024)
This study aims to evaluate the feasibility of using discovery learning-based student worksheets (LKPD) to foster CTS in the context of acid-base topics. The feasibility of the LKPD is assessed through three key criteria: validity, practicality, and effectiveness. The worksheets incorporate critical thinking skills (CTS) such as interpretation, evaluation, analysis, and inference, applied to understanding acid-base properties and strength. A one-group pretest-posttest design was used, involving 22 students from class XI-4 at SMAN 1 Kedamean, Gresik. Research instruments included response questionnaires, student activity observation sheets, and pretest-posttest assessments for CTS and cognitive learning outcomes. The results revealed the following: (1) Practicality was supported by student activity observations, with a higher proportion of relevant activities and 93.33% of students giving positive feedback, categorizing the LKPD as very practical. (2) The LKPD received a validity score of 4. (3) Effectiveness was demonstrated through pretest-posttest results, with 90.9% of students achieving classical completeness and an n-gain of 0.7 for critical thinking skills, rated as high. Based on these results, the discovery learning-based LKPD is considered feasible.